Formation of Catalytic Layer for Fuel Cells with Low Platinum Content; The 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Sokhoreva V. V. Valentina Viktorovna (Power System and Renewable Energy, 2014)
Title screen